Vitrification Ability of Combined and Single Cryoprotective Agents - Faltus, Milos; Bilavcik, Alois; Zamecnik, Jiri (Plants (Basel, Switzerland), 2021)
Cryoprotective agents (CPA) are an important part of many current vitrification methods. The vitrification ability of CPAs influences the probability of the glass transition and water crystallization occurrence. Thermal characteristics and the vitrification ability of two combined CPAs (PVS2 and PVS3), common plant vitrification solutions, and four single CPAs (ethylene glycol, DMSO, glycerol, and sucrose), the components of the mentioned PVSs, were evaluated utilizing a differential scanning calorimetry (DSC) during standard cooling/warming rates of 10 °C min-1. The effect of solute concentration on their vitrification ability was shown in the CPAs tested. Four typical concentration regions at which the glassy state and/or crystallization occurred were defined. We suggest the solute concentration of 0.7 g g-1 as the universal vitrification concentration, characterized by an actual Tg of CPA solution and limited water crystallization. Knowledge of the thermal properties of CPAs allows the design of new combined CPAs with the required vitrification ability respecting the cryopreservation method used and the characteristics of the cryopreserved sample.
Keywords: cryoprotectant; differential scanning calorimetry; glass transition; vitrification; cryopreservation; water crystallization